Special features of mathematical modelling of chemical and mass transfer processes - L. A. Serafimov; T. V. Chelyuskina; A. K. Frolkova (Тонкие химические технологии, 2014)
Some problems of mathematical modeling of distillation and chemical processes were discussed. The common and distinguishing features of these processes were revealed. The possibility of using the method of dynamical systems for studying these objects was shown, and some of special characteristics were revealed.